2015
DOI: 10.1210/jc.2014-3016
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-Hydroxyvitamin D and Adipose Tissue Vitamin D Receptor Gene Expression: Relationship With Obesity and Type 2 Diabetes

Abstract: 25(OH)D levels are diminished in P&D compared to NG subjects, independently of BMI, and are closely related to glucose metabolism variables, suggesting that vitamin D deficiency is associated more with carbohydrate metabolism than with obesity. Moreover, AT has a different response to 1,25(OH)2D3 depending on the degree of obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
62
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 20 publications
10
62
1
3
Order By: Relevance
“…However, the association is still inconsistent (21). Moreover, we found a negative association between 25(OH)D and WC, WHtR, and %FM that was similar to the findings of previous studies (22,23).…”
Section: Discussionsupporting
confidence: 88%
“…However, the association is still inconsistent (21). Moreover, we found a negative association between 25(OH)D and WC, WHtR, and %FM that was similar to the findings of previous studies (22,23).…”
Section: Discussionsupporting
confidence: 88%
“…The considerable host of actions performed by PPARG can be compared to those of vitamin D and VDR [15], which has been implicated in neurologic disorders [1618], autoimmune pathologies [1921], cardiovascular disease [22], diabetes mellitus [23, 24], psoriasis [15] or infectious disease [25, 26], and, above all of what is mentioned, cancer [27, 28]. …”
Section: The Pparg Physiologymentioning
confidence: 99%
“…Clemente-Postigo et al [62] discovered an inverse association between serum concentrations of 25-hydroxyvitamin D, 1,25-dihydroxyvitamin D, and the parameters of insulin resistance, such HOMA-IR and plasma glucose levels, in patients with obesity. In a study using premenopausal women, Ferreira et al [63] showed a negative correlation between serum vitamin D levels and parameters of insulin resistance.…”
Section: Vitamin D and Insulin Resistance In Obesitymentioning
confidence: 99%